Assessing the Continuity and Sequence of Geography Curriculum: A Case of Physical Geography at Bachelor`s and Master's Degree at Tribhuvan University, Nepal - Linkha, Tika Ram (Patan Gyansagar, 2025)
This study examines the continuity and sequence in the geography curriculum at bachelor’s and master’s levels in Tribhuvan University. The learners are facing various learning difficulties in the classroom but insufficient attention has been paid to the curriculum. Why learners feel problems understanding any part of the courses is still an unexplored issue in this context, this study highlighted the importance of continuity and sequence in the curriculum. It is based on secondary information collected from various journals, books and the present curriculum of geography at both levels from the Dean`s office of the faculties of Humanities and Social Science, TU. The study reveals that there is a commendable degree of continuity and progression across the bachelor's and master's levels, ensuring students build on foundational concepts while exploring advanced applications. However, there is a lack of a specification table and an absence of teaching methods in the curriculum. Moreover, a lack of standard criteria for internal evaluation causes inconsistent marking. This study will be useful and serve as a roadmap for curriculum designers in the future at the university level since it reveals the gaps in continuity and sequence in the curriculum of these specific courses.